PERANCANGAN DAN IMPLEMENTASI SISTEM MEJA GAMBAR DENGAN METODE XY-TABLE 2 SUMBU MENGGUNAKAN MOTOR STEPPER DAN EMC - Linggarjati, Jimmy; Aldiansyah, Arif; Sutanto, Daniel; Imanullah, Otto Hidayat (Bina Nusantara University, 2007)
The objective of the research was to produce a drawing table system with 2-aksis XY-table method and EMCsoftware implementation. The EMC (Enhanced Machine Control) features are integrated with L297 and L298 as a motorstepper driver to draw simple objects. Methods used in the research are library research, engineering, and laboratory.The results concluded that system can work properly to draw objects such as square, triangle, circle, and capital lettersA-Z according to the given input.